Regulation of nitrogenase synthesis in histidine auxotrophs of Klebsiella pneumoniae with altered levels of adenylate nucleotides. - Stougaard, J (1988)
A histidine auxotrophic (hisA) mutant of Klebsiella pneumoniae is phenotypically Nif- when grown with 20 micrograms of histidine ml-1 but Nif+ when supplied with histidine at 100 micrograms ml-1. Reversion to Nif+ at 20 micrograms of histidine ml-1 occurs phenotypically by the addition of 2-thiazolyl-DL-alanine or genetically by mutation in hisG; 2-thiazolyl-DL-alanine inhibits and hisG encodes phosphoribosyl phosphotransferase, the first enzyme of the histidine biosynthetic pathway which consumes ATP. Physiological studies of the hisA mutant JS85 showed that after removal of NH4+ from a culture of the mutant grown with 20 micrograms of histidine ml-1, synthesis of nitrogenase polypeptides occurred at a rate similar to that in the wild type for about 3 h and acetylene reduction activity reached about 10% of the fully derepressed wild-type level. Shortly thereafter the concentration of intracellular adenylates decreased; in particular, ATP fell to about 10% of normal levels. Also, nitrogenase proteins (nifHDK products) and the nifJ gene product stopped being synthesized. These effects were not due to impairment of growth or protein synthesis by histidine starvation. Inhibition of phosphoribosyl phosphotransferase with 2-thiazolyl-DL-alanine restored nitrogenase activity and synthesis, indicating that the effect of the hisA mutation on nif expression was probably a consequence of lowered energy resources that occurred during anaerobic N starvation. The loss of ATP was not associated with nitrogenase synthesis or activity, since hisA nifA and hisA nifH double mutants underwent a loss of ATP in derepressing conditions. Transcription from the nifL, nifN, and nifH promoters was examined in hisA strains with Mu d(Ap lac) fusions in these nif genes. Transcription was not significantly influenced under conditions where adenylates were decreased in concentration. Also nif mRNA apparently accumulated in cultures unable to synthesize nitrogenase, suggesting that translational control of nif gene product synthesis occurs under unfavorable energetic conditions.